(untitled) (Research, Society and Development, 2022)
This article presents a reflection with theoretical references that discuss how technologies are associated in an inclusive perspective in the work with Target Audience students of Special Education, and how they collaborate in pedagogical practices. In order to understand the importance of technology in education, analyze the legal contributions in the field of inclusive education on the use of technologies in Basic Education, seeking to highlight the benefits of Digital Technologies of Information and Communication in pedagogical practices for inclusion and schooling of students with disabilities. The research is bibliographical, and documentary and its methodological approach is qualitative. It is important to think about the use of technologies for students with disabilities so that inclusion takes place in the planning and practices of teaching and learning. The research demonstrates that the use of Information and Communication Technologies is one of the ways to be adopted for the organization of teaching, whether in regular teaching in a common classroom or in the extracurricular shift in Multifunctional Resource Rooms, as it promotes the development of complex thinking functions.